Spatial heterogeneity of food web structure driven by glacial retreat in Marian Cove, Antarctica: linking environmental DNA interconnections - Kyu-Young Shim; In-Cheol Yeo; Jun-Oh Min; Jeong-Hoon Kim; Sun-Yong Ha; Chang-Bum Jeong (Marine Life Science & Technology, 2026)

Biochemical composition and bioavailability of sedimentary organic matter in two contrasting intertidal flats of Korea - Mi Sun Yun; Su In Kim; Jun-Oh Min; Sun-Yong Ha; Jae Hyeok Shin; Sunghan Kim; Seung-Il Nam; Ho Kyung Ha (Marine Pollution Bulletin, 2026)

Spatiotemporal distributions of total and methylmercury in bivalves from coastal zones of South Korea - Haein Yu; Geonwoo Park; Chul-In Sun; Yong Hwa Oh; Yong-Woo Lee (Marine Pollution Bulletin, 2025)

ELF18-INDUCED LONG NONCODING RNA 25 positively regulates the pathogen defense-related CYP82C2 expression in Arabidopsis - Jun Sung Seo; Moon-Joo Lee; Jimin Lee; Nuri Oh; So-Young Jang; Ye In Cho; Jin-Ho Kang; Jang-Kyun Seo; Hye Sun Cho; Moonhyuk Kwon; Choonkyun Jung (Journal of Plant Biology, 2025)
Long noncoding RNAs (lncRNAs) are emerging as important regulators of gene expression during plant immune responses. In this study, we identified a novel lncRNA, ELF18-INDUCED LONG NONCODING RNA 25 ( ELENA25 ), located in the intergenic region between AT4G31960 and CYTOCHROME P450, family 82, subfamily C, polypeptide 2 ( CYP82C2 ) in Arabidopsis. ELENA25 was initially identified through custom lncRNA microarray data. Here, its full-length sequence (810 bp) was determined using primer walking and confirmed by sequencing. ELENA25 expression was preferentially induced by flg22, a bacterial pathogen-associated molecular pattern (PAMP), in a late-phase and FLS2 receptor-dependent manner. Neighboring genes AT4G31960 and CYP82C2 were also flg22-inducible, with expression abolished in the fls2 mutant background. To assess whether ELENA25 regulates the expression of nearby genes, we generated ELENA25 -overexpressing (OX) and knockout (KO) plants. In ELENA25 OX lines, CYP82C2 expression was significantly upregulated under normal and flg22-treated conditions, while AT4G31960 expression remained unchanged. Conversely, in the elena25 mutants (KO), CYP82C2 expression was significantly reduced, indicating that ELENA25 positively regulates CYP82C2 transcription. Expression levels of other nearby cytochrome P450 genes, including CYP82C3 and CYP82C4 , and other indole glucosinolate-related CYP genes were not affected by ELENA25 expression changes. Collectively, our results demonstrate that ELENA25 is a flg22-inducible lncRNA that specifically enhances CYP82C2 expression in a FLS2-dependent manner. This study provides new insights into the role of lncRNAs in plant innate immunity, highlighting ELENA25 as a positive regulator of defense-related gene expression.

Bioconversion of citrus waste into mucic acid by xylose-fermenting Saccharomyces cerevisiae - Deokyeol Jeong; Sujeong Park; Grace Evelina; Suhyeung Kim; Heeyoung Park; Je Min Lee; Sun-Ki Kim; In Jung Kim; Eun Joong Oh; Soo Rin Kim (Bioresource Technology, 2024)

In situ fabrication of Ag decorated porous ZnO photocatalyst via inorganic–organic hybrid transformation for degradation of organic pollutant and bacterial inactivation - Min Seok Song; Ruturaj P. Patil; In Seon Hwang; Mahadeo A. Mahadik; Tae-Hu Jang; Byung Taek Oh; Weon-Sik Chae; Sun Hee Choi; Hyun Hwi Lee; Jum Suk Jang (Chemosphere, 2023)

Influence of ultrafast microwave deposition on morphology and growth mechanism of WO3 nanosheet photoanode for efficient bacterial inactivation and decomposition of organic pollutants - In-Seon Hwang; Mahadeo A. Mahadik; Min Seok Song; Se-Won Lee; Byung-Taek Oh; Hyun Hwi Lee; Weon-Sik Chae; Sun Hee Choi; Jum Suk Jang (Journal of Environmental Chemical Engineering, 2023)

Clinical features and epidemiology of severe fever with thrombocytopenia syndrome in dogs in the Republic of Korea: an observational study (2019–2020) - Sun-Woo Han; Ye-In Oh; Ji-Min Rim; Yoon-Kyoung Cho; Dong-Hoo Kim; Jun-Gu Kang; Kyoung-Seong Choi; Joon-Seok Chae (Veterinary Research Communications, 2022)

First report of powdery mildew caused by Erysiphe polygoni on Rumex japonicus in Korea - In-Young Choi; Hyun-Myung Oh; Sun-Hee Hong; Young-Ho Lee; Hyeon-Dong Shin (Journal of Plant Pathology, 2022)

A preliminary study of natural environmental change and its impact on early Late Paleolithic people in the northeast central Korean Peninsula during Marine Istope Stage 3 (40–30k cal a bp ) - Sangheon Yi; Chang‐Gyun Han; Keun‐Chang Oh; In Sun Seo; Dongwook Kim; Jaeyoung Lee; Min Han; Hanwoo Choi; Jaesoo Lim; Sujeong Park; Chang‐Pyo Jun; Taesop Cho (Journal of Quaternary Science, 2022)
We comprehensively analyzed sediments obtained from an archeological excavation. A trench sediment profile of Maedun Cave (MC), South Korea, was analyzed geoarchaeologically. Multi‐proxy analyses (palynomorphs, grain size, magnetic susceptibility, animal bones and artifacts) reflected the vegetation, hydroclimate and lives of prehistoric people at Marine Isotope Stage (MIS) 3 (ca. 40–30k cal a bp ) in the early Late Paleolithic. The palynoflora consisted of pollen and non‐pollen palynomorphs. Under the air‐circulation system in the cave, anemophilous pollen flowed in during the day, whereas waterborne pollen and spores, and freshwater algae, were transported by flooding during the summer monsoon rainy season. Mixed conifer and deciduous broad‐leaved forest with an understory of pteridophytes flourished around the north‐east central Korean Peninsula during MIS 3. Freshwater algae and grass pollen records may reflect precipitation intensity. It is assumed that they had flowed in during flooding caused by high precipitation during the enhanced East Asian summer monsoon, corresponding to Dansgaard–Oeschger (D/O) events 5 and 8 of δ 18 O GISP2 and Hulu Cave. The prehistoric people hunted herbivorous animals in the area around MC and sheltered inside it seasonally. They also used the grains of oats growing near the dwelling as a source of food.

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Comparison of the clinical characteristics and outcomes of bloodstream infections caused by Raoultella species and Klebsiella pneumoniae - Kyung-Wook Hong; Yun-Hong Cheon; Kyunglan Moon; Sun In Hong; Byung-Han Ryu; Oh-Hyun Cho; In-Gyu Bae (Infectious Diseases, 2020)

In Situ Gelling Hydrogel with Anti-Bacterial Activity and Bone Healing Property for Treatment of Osteomyelitis - Sun Woo Jung; Se Heang Oh; In Soo Lee; June-Ho Byun; Jin Ho Lee (Tissue Engineering and Regenerative Medicine, 2019)

Inappropriate empirical antibiotic therapy does not adversely affect the clinical outcomes of patients with acute pyelonephritis caused by extended-spectrum β-lactamase-producing Enterobacteriales - Si-Ho Kim; Suhyun Oh; Kyungmin Huh; Sun Young Cho; Cheol-In Kang; Doo Ryeon Chung; Kyong Ran Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Twelve-year trend in the use of zolpidem and physicians’ non-compliance with recommended duration: a Korean national health insurance database study - Yunjeung Jang; Inmyung Song; In-Sun Oh; Ju-Young Shin (European Journal of Clinical Pharmacology, 2019)

Identification of a molecular marker tightly linked to bacterial wilt resistance in tomato by genome-wide SNP analysis - Boyoung Kim; In Sun Hwang; Hyung Jin Lee; Je Min Lee; Eunyoung Seo; Doil Choi; Chang-Sik Oh (Theoretical and Applied Genetics, 2018)

Bladder reconstruction using stem cells seeded on multilayered scaffolds in a mucosa preserving partial cystectomy model - Kshitiz Raj Shrestha; Yong Hyun Park; Yong Sun Choi; In Gul Kim; Shuyu Piao; Ae Ryang Jung; Seung Hwan Jeon; Se Heang Oh; Jin Ho Lee; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2015)

Shoot elongation and gibberellin contents in Cyclamen persicum are influenced by temperature and light intensity - Wook Oh; Jiseon Kim; Yoon Ha Kim; In-Jung Lee; Ki Sun Kim (Horticulture, Environment, and Biotechnology, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

N-terminal region of rice polycomb group protein OsEZ1 is required for OsEZ1–OsFIE2 protein interaction - Jong-Kuk Na; Mi-Hye Seo; Seok-Jun Moon; In-Sun Yoon; Yeon-Hee Lee; Jae Kwang Kim; Kyun Oh Lee; Dool-Yi Kim (Plant Biotechnology Reports, 2013)

Involvement of rice Polycomb protein OsFIE2 in plant growth and seed size - Jong-Kuk Na; Mi-Hye Seo; In-Sun Yoon; Yeon-Hee Lee; Kyun Oh Lee; Dool-Yi Kim (Plant Biotechnology Reports, 2012)

Expression of the protective antigen for PEDV in transgenic duckweed, Lemna minor - Suk-Min Ko; Hyeon-Jin Sun; Myung Jin Oh; In-Ja Song; Min-Jae Kim; Hyun-Sook Sin; Chang-Hyo Goh; Yong-Woo Kim; Pyung-Ok Lim; Hyo-Yeon Lee; Suk Weon Kim (Horticulture, Environment, and Biotechnology, 2011)

Superoxide anion regulates plant growth and tuber development of potato - Mi-Sun Kim; Hyun-Soon Kim; Yoon-Shik Kim; Kwang-Hyun Baek; Hyun-Woo Oh; Kyu-Woong Hahn; Ro-Na Bae; In-Jung Lee; Hyouk Joung; Jae-Heung Jeon (Plant Cell Reports, 2007)

Enhanced brain targeting efficiency of intranasally administered plasmid DNA: an alternative route for brain gene therapy - In-Kwon Han; Mi Young Kim; Hyang-Min Byun; Tae Sun Hwang; Jung Mogg Kim; Kwang Woo Hwang; Tae Gwan Park; Woon-Won Jung; Taehoon Chun; Gil-Jae Jeong; Yu-Kyoung Oh (Journal of Molecular Medicine, 2006)

Light- and electron-microscopic analysis of neuropeptide Y-immunoreactive amacrine cells in the guinea pig retina - Wha-Sun Kang; Min-Young Lim; Eun-Jin Lee; In-Beom Kim; Su-Ja Oh; Nicholas C. Brecha; Cheol-Beom Park; Myung-Hoon Chun (Cell and Tissue Research, 2001)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)